Self-Correction Sensor for Measuring Medium DC Voltage Based on Resistance Voltage Divider - Xiaojun Tang; Pan Pan; Feng Zhang; Ling Yan; Yangyu Lyu; Yi Wu; Mingzhe Rong; Berihun Gebreyohannes Teklu (CSEE Journal of Power and Energy Systems)
With the rapid development of the direct current (DC) distribution network, DC voltage measurement technology is increasingly important to ensure safe operation in the distribution network. The measurement accuracy of the traditional sensor based on resistance dividers decreases over time because the resistors age due to temperature and electromagnetic radiation. To address this problem, a novel type of medium-voltage DC voltage sensor with self-correction ability is presented in this paper. A resistor with large <tex>$R_{H}$</tex> is connected in series with <tex>$R_{K}$</tex> and <tex>$R_{G}$</tex>, i.e. two precise resistors with low resistance, to transform the measured medium voltage into low voltage. Among these three resistors in the divider, <tex>$R_{H}$</tex> connects with the measured medium DC line, while <tex>$R_{G}$</tex> connects with the ground. An electronic switch, K, is paralleled with <tex>$R_{K}$</tex>, the precise resistor at the middle position. Generally, the state of the electronic switch is off, and the current flows through <tex>$R_{K}$</tex>. Medium DC voltage can be measured according to the voltage on <tex>$R_{G}$</tex> with the divider ratio. When the sensor needs self-correction, the electronic switch will be controlled by FPGA (Field Programmable Gate Array) to turn it off and on; therefore, two values of low voltage can be obtained using time-sharing sampling. Two equations can be built according to the divider principle, and <tex>$R_{H}$</tex> in the divider can be evaluated by solving the equations. As a result, the measurement error caused by the change in <tex>$R_{H}$</tex> can be avoided. Finally, the medium-voltage DC sensor developed in this paper has been tested at the Institute of High Voltage, Wuhan, China. The experimental results show that the sensor can perform self-correction without manual operation, and the sensor's accuracy can reach 0.12%. Sensors with a self-calibration function can realize long-term high-precision measurement without manual maintenance, showing a good application prospect.